The Relationship Between Peer Social Support and Academic Resilience in Final Year Students - Tadjuddin, Indah Lestari (Jurnal Indonesia Sosial Sains, 2025)
Social support between students in completing the final project makes students' academic resilience increase. This study aims to determine the relationship between peer social support and academic resilience in final year students of the Faculty of Health Sciences, University of 'Aisyiyah Yogyakarta. This research method uses a quantitative approach. The research population is all final semester students of the Faculty of Health Sciences, University of 'Aisyiyah Yogyakarta who are in the age range of 20-24. The sampling technique uses the convience sampling technique.The results showed that there was a relationship between peer social support and academic resilience in final year students of the Faculty of Health Sciences, University of 'Aisyiyah Yogyakarta, which was shown with a significance value of 0.000<0.05. Furthermore, the value of peer social support contribution to effective academic resilience was 60.2%, while the remaining 39.8% was influenced by other factors that could affect academic resilience variables.